Comparison of acellular dermal matrix allograft (ADMA) and a subepithelial connective tissue graft (SCTG) for the treatment of gingival recession - Niloofar Jenabian; Mohadese Yazdanpanahbahabadi; Parya Haghpanah Aski; Ali Bijani (Tabriz University of Medical Sciences, 2020)
Background. This study aimed to evaluate the effect of acellular dermal matrix allograft (ADMA) for the treatment of gingival recession as a substitute for subepithelial connective tissue graft (SCTG). Methods. In this controlled clinical trial, 18 teeth were selected in nine subjects with bilateral gingival recession. One side was treated with SCTG and a coronally displaced flap as the control group, and the other side was treated with ADMA and a coronally displaced flap as the test group. Probing pocket depth (PPD), clinical attachment level, vertical recession depth, recession width, gingival thickness, keratinized tissue width, and the root coverage percentage were measured before the surgery and at 1-, 3-, and 6-month postoperative intervals. The healing index, pain index, and patient satisfaction were also investigated. The data were analyzed with a general linear model (GLM) repeated measures and paired t-test. Results. All the parameters improved except for PPD; however, a comparison between the groups did not reveal statistically significant differences. Only root coverage percentage and pain index were significantly lower in the test group. The average percentage of root coverage in the control and test groups were 82.01±16.62% and 64.44±9.4%, respectively. Conclusion. Both methods resulted in improvements in the clinical results. However, the use of the ADMA led to less pain and root coverage in comparison with the SCTG method.